Predicted Vancomycin Dosage Requirement in Patients With Hematological Malignancies and Dosage Dynamic Adjustment - Song, Xiangqing; Wu, Yi (Frontiers in Pharmacology, 2022)
Purpose: The purpose of this study was (1) to predict requisite vancomycin daily dose (Dvan) used in the target patients suffering from both bacterial infection and hematological malignancies, and (2) to construct a vancomycin-dose-graphical tool to assist clinicians to develop vancomycin dosing regimens, and further (3) to establish a programming process for vancomycin dynamic dosage adjustment to help clinicians to adjust vancomycin dosing regimens according to physiological and pathogenic factors of the target patients. Methods: Established the Dvan model associated with microbial susceptibility, vancomycin pharmacokinetic and dosing parameters, and estimated the Dvan based on the established Dvan model and using Monte Carlo simulations. Dvan achieving 90% of probability of target attainment (PTA) for bacterial isolate or cumulative fractions of response (CFR) for bacterial population at a ratio of daily area under curve (AUC24) to the minimum inhibitory concentration (MIC) [i.e., AUC24/MIC] of 400～600 was considered sufficient to treat infection occurring in the target patients. On the basis of the predicted Dvan, the physiological states of patients and the pathogenic variables of infection, a vancomycin-dose-graphical tool for the target patients and a programming process for vancomycin dynamic dosage adjustment were constructed. Results: This study predicted requisite Dvan used in patients suffering from both bacterial infection and hematological malignancies, and constructed a vancomycin-dose-graphical tool for the target patients, at different physiological states and pathogenic variables, to formulate vancomycin dosing regimens. Also, this study established and expounded the formulation process of vancomycin dosage dynamic adjustment according to fluctuant renal function of the target patients. Conclusions: With the tools, the required Dvan or vancomycin dosing regimens for the target patients, at different physiological states and pathogenic variables, can be readily known, whether or not vancomycin dynamic dosage adjustment is required.